Parametric analysis of pitch angle scattering and losses of relativistic electrons by oblique EMIC waves - Hanzelka, Miroslav; Li, Wen; Ma, Qianli (Frontiers in Astronomy and Space Sciences, 2023)
We analyze the effects of electromagnetic ion cyclotron (EMIC) waves on relativistic electron scattering and losses in the Earth's outer radiation belt. The EMIC emissions are commonly observed in the inner magnetosphere and are known to reach high amplitudes, causing significant pitch angle changes in primarily >1 MeV electrons via cyclotron resonant interactions. We run test-particle simulations of electrons streaming through helium-band waves with different amplitudes and wave normal angles and assess the sensitivity of advective and diffusive scattering behavior to these two parameters, including the possibility of very oblique propagation. The numerical analysis confirms the importance of harmonic resonances for oblique waves, and the very oblique waves are observed to efficiently scatter both co-streaming and counter-streaming electrons. However, strong finite Larmor radius effects limit the scattering efficiency at high pitch angles. Recently discussed force bunching effects and associated strong positive advection at low pitch angles are, surprisingly, shown to cause no decrease in the phase space density of precipitating electrons, and it is demonstrated that the transport of electrons into the loss cone balances out the scattering out of the loss cone. In the case of high-amplitude obliquely propagating waves, weak but nonnegligible losses are detected well below the minimum resonant energy, and we identify them as the result of nonlinear fractional resonances. Simulations and theoretical analysis suggest that these resonances might contribute to subrelativistic electron precipitation but are likely to be overshadowed by nonresonant effects.